Basic Questioning Skills in Islamic Education Subjects at State Junior High School 13 Pontianak - Rianawati Rianawati; Juliani Sartika; Sulaiman Sulaiman; Yapandi Ramli (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2020)
This research was motivated by the lack of effectiveness of teachers in applying skill in asking questions on Islamic Education subjects at State Junior High School(SMPN) 13 Pontianak. The study aims to find out, 1) How is the application of basic questioning skills components by teachers in islamic education subjects at SMPN 13 Pontianak? 2) Do teachers do things that should be avoided in applying basic questioning skills to Islamic Education subjects at SMPN 13 Pontianak? This research uses descriptive method and qualitative approach. The research was conducted at SMP Negeri 13 Pontianak. The subject of this research was a teacher of Islamic education at SMP Negeri 13 Pontianak. Data collection techniques used are observation, interview, and documentation. Data analysis techniques used in this research are data reduction, data display, and conclusion drawing. The data validity examination techniques used in this study are data triangulation, member check, deep observation and using reference material. Based on the results of the research, it can be concluded that the teacher's questioning skills are the most frequent and most important activity carried out in the learning process. The ability to ask questions is the main ability that must be possessed by teachers because asking is a tool for teaching. 1) The application of basic questioning components, namely clear and brief question disclosure, reference, concentration in questioning skills, transfer of answering turns, dissemination of questions, giving thought time in asking questions and giving demands have been implemented and carried out by PAI teachers in the learning process. 2) Teachers do things that should be avoided in questioning skills.